2007
DOI: 10.1007/s11270-007-9590-y
|View full text |Cite
|
Sign up to set email alerts
|

Input–Output Budgets for Inorganic Nitrogen Under Acid Rain in a Subtropical Evergreen Mixed Forest in Central-South China

Abstract: Inorganic nitrogen deposition and leaching in stream water were monitored from January, 2001 to December, 2004 in a subtropical evergreen mixed forest in central-south China. The seasonal concentration and flux of inorganic nitrogen in bulk precipitation and stream water, seasonal mean net retention of nitrogen and net flux of H + transformed by nitrogen were estimated and quantified in Shaoshan forest. The research results show that the correlation coefficient of fluxes between bulk precipitation and stream w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
(50 reference statements)
0
12
0
1
Order By: Relevance
“…However, the generalization of this statement for other forest ecosystems should be avoided, given the shortcomings of our empirical approach to modeling acid rain effects (see the following section Simulation limitations). Rain pH values lower than 4.0 are unusual in most of southeastern China (Du et al 2008;Fan and Hong 2001) and have been reported only in the vicinity of main polluting sources (Fan and Wang 2000). As direct physical damage by acid rain on plant tissues has not been observed at pH values higher than 3.5 (Kennedy 1992;Liu et al 2010b), the expected influence of acid pollution in this region will be produced by indirect effects on Table 2.…”
Section: Effects Of Atmospheric Pollution On Biomass Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the generalization of this statement for other forest ecosystems should be avoided, given the shortcomings of our empirical approach to modeling acid rain effects (see the following section Simulation limitations). Rain pH values lower than 4.0 are unusual in most of southeastern China (Du et al 2008;Fan and Hong 2001) and have been reported only in the vicinity of main polluting sources (Fan and Wang 2000). As direct physical damage by acid rain on plant tissues has not been observed at pH values higher than 3.5 (Kennedy 1992;Liu et al 2010b), the expected influence of acid pollution in this region will be produced by indirect effects on Table 2.…”
Section: Effects Of Atmospheric Pollution On Biomass Productionmentioning
confidence: 99%
“…Southern China also has some of the highest nitrogen deposition rates in the world, with rates similar to those of central Europe and eastern North America (Du et al 2008). Usual values range from 7 kg N·ha -1 ·year -1 in rural areas to 30 kg N·ha -1 ·year -1 in industrial areas, reaching in particular locations 50 kg N·ha -1 ·year -1 and above (Chen and Mulder 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…And, in eastern Asia and in China in particular, coal fired power plants-a key contributor to acid deposition-are a widespread and rapidly increasing energy source. Although not historically highlighted as an environmental issue in this region, there may be an increasing need to consider both stream acidification with habitat when managing stream fisheries there and in other areas of in the developing world (Kuylenstierna 2001;Du 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the N status, dynamics and leaching risk in these subtropical forests in China. Du et al (2008) reported a high N deposition of 26.23 kg N ha -1 year -1 in a subtropical forest over four years in the central China, in which no symptoms of N saturation were occurred and no indication of forest productivity declination was shown. The forest ecosystems of subtropical China may be different from those in temperate and boreal regions due to the different climate, species composition and soil properties.…”
Section: Introductionmentioning
confidence: 99%